Gamete therapeutics: recombinant protein adsorption by sperm for increasing fertility via artificial insemination. - Horacio Alvarez-Gallardo; Michael E Kjelland; Juan F Moreno; Thomas H Welsh; Ronald D Randel; Miguel A Lammoglia; Mario Pérez-Martínez; Alma V Lara-Sagahón; A Enrique Esperón-Sumano; Salvador Romo (PLoS ONE, 2013)
A decrease in fertility can have a negative economic impact, both locally and over a broader geographical scope, and this is especially the case with regard to the cattle industry. Therefore, much interest exists in evaluating proteins that might be able to increase the fertility of sperm. Heparin binding proteins (HBPs), specifically the fertility associated antigen (FAA) and the Type-2 tissue inhibitor of metalloproteinase (TIMP-2), act to favor the capacitation and acrosome reaction and perhaps even modulate the immune system's response toward the sperm. The objective of this research was to determine the effect on fertility of adding recombinant FAA (rFAA) and recombinant TIMP-2 (rTIMP-2) to bovine semen before cryopreservation for use in an artificial insemination (AI) program in a tropical environment. For this experiment, 100 crossbred (Bos taurus x Bos indicus) heifers were selected based on their estrus cycle, body condition score (BCS), of 4 to 6 on a scale of 1 to 9, and adequate anatomical conformation evaluated by pelvic and genital (normal) measurements. Heifers were synchronized using estradiol benzoate (EB), Celosil® (PGF2α) (Shering-Plough) and a controlled internal drug release (CIDR) device was inserted that contained progesterone. Inseminations were performed in two groups at random, 50 animals per group. The control group was inseminated with conventional semen. The treatment group was inseminated with semen containing rFAA (25 µg/mL) and rTIMP-2 (25 µg/mL). In the control group a 16% pregnancy rate was obtained versus a 40% pregnancy rate for the HBP treatment group, resulting in a significant difference (P = 0.0037). Given the results herein, one may conclude that the HBPs can increase fertility and could be an option for cattle in tropical conditions; however, one needs to consider the environment, nutrition, and the genetic interaction affecting the final result in whatever reproductive program that is implemented.